Impact of childhood traumatic brain injury on fitness for service class, length of service period, and cognitive performance during military service in Finland from 1998 to 2018: A retrospective register-based nationwide cohort study - Möttönen, Julius; Ponkilainen, Ville T.; Mattila, Ville M.; Kuitunen, Ilari (PloS one, 2024)
Traumatic brain injury (TBI) can cause neuronal damage and cerebrovascular dysfunction, leading to acute brain dysfunction and considerable physical and mental impairment long after initial injury. Our goal was to assess the impact of pediatric TBI (pTBI) on military service, completed by 65-70% of men in Finland. We conducted a retrospective register-based nationwide cohort study. All patients aged 0 to 17 years at the time of TBI, between 1998 and 2018, were included. Operatively and conservatively treated patients with pTBI were analyzed separately. The reference group was comprised of individuals with upper and lower extremity fractures. Information on length of service time, service completion, fitness for service class, and cognitive performance in a basic cognitive test (b-test) was gathered from the Finnish Military Records for both groups. Linear and logistic regression with 95% CI were used in comparisons. Our study group comprised 12 281 patients with pTBI and 20 338 reference group patients who participated in conscription. A total of 8 507 (66.5%) men in the pTBI group and 14 953 (71.2%) men in the reference group completed military service during the follow-up period. Men in the reference group were more likely to complete military service (OR 1.26, CI 1.18-1.34). A total of 31 (23.3%) men with operatively treated pTBI completed the military service. Men with conservatively treated pTBI had a much higher service rate (OR 7.20, CI 4.73-11.1). In the pTBI group, men (OR 1.26, CI 1.18-1.34) and women (OR 2.05, CI 1.27-3.36) were more likely to interrupt military service than the reference group. The PTBI group scored 0.15 points (CI 0.10-0.20) less than the reference group in cognitive b-test. PTBI groups had slightly shorter military service periods and higher interruption rate than our reference-group. There were only minor differences between groups in cognitive b-test.